International debt statistics 2013 (Global Development Finance, 2012)
International Debt Statistics (IDS) 2013 is a continuation of the World Bank?s publications Global Development Finance, Volume II (1997 through 2009) and the earlier World Debt Tables (1973 through 1996). IDS 2013 provides statistical tables showing the external debt of 128 developing countries that report public and publicly guaranteed external debt to the World Bank?s Debtor Reporting System (DRS). It also includes tables of key debt ratios for individual reporting countries and the composition of external debt stocks and flows for individual reporting countries and regional and income groups along with some graphical presentations. IDS 2013 draws on a database maintained by the World Bank External Debt (WBXD) system. Longer time series and more detailed data are available from the World Bank open databases, which contain more than 200 time series indicators, covering the years 1970 to 2011 for most reporting countries, and pipeline data for scheduled debt service payments on existing commitments to 2019. International Debt Statistics 2013 is unique in its coverage of the important trends and issues fundamental to the financing of the developing world. This report is an indispensible resource for governments, economists, investors, financial consultants, academics, bankers, and the entire development community. In addition, International Debt Statistics will showcase the broader spectrum of debt data collected and compiled by the World Bank. These include the high frequency, quarterly external debt database (QEDS) and the quarterly public sector database (QPSD) developed in partnership with the International Monetary Fund and launched by the World Bank.